Pulse profile and metal transfer in pulsed gas metal arc welding: droplet formation, detachment and velocity. (3rd October 2017) - Dos Santos, Emanuel B. F.; Pistor, Rob; Gerlich, Adrian P.
ABSTRACT: The influence of current profile and pulse parameters on droplet formation and transfer was investigated. One profile has an exponential ramp up and down in the current pulse shape, while the second is nearly square shaped. High-speed photography, synchronised with a high-speed data acquisition system, was used to monitor the droplet formation and transfer. It was found that for long-tail current profile, most of droplet formation and detachment occurs before background current is reached. While, for the nearly square pulse, most of droplet formation and transfer occurs during background current, giving a stable and smooth metal transfer. The arc attachment position was found to vary for the different profiles. Droplet speed was measured, and it was found that it is proportional to the peak current and inversely proportional to background current. Dimensionless process parameters were defined and used to predict droplet speed using a neural networks algorithm.